Improvement of Volvo's police cars regarding storage and the dog crate - Brorsson Pierre, Pontus (2012)
This report describes the process and the result of a master thesis in industrial design engineering at Luleå University of Technology. The thesis was carried out at Volvo Car Corporation, Special Vehicles, at the department for commercial vehicles, in Gothenburg during October 2011 to Mars 2012. The aim of the project was to come up with concepts for improvements of today’s police car, in terms of the design of the dog crate and general storage. According to customer surveys about police cars made by Volvo, storage is a very important area with potential for improvement. Regarding the dog crate many police officers have come with specific requests for improvements, mostly regarding size and sound. The project started with an extensive preliminary study where police districts all around Sweden were visited. During the visits police officers and dog handlers were interviewed and surveys were handed out. This resulted in great knowledge for the present situation and many problems and possibilities for improvements were found. The majority of the major problems found were related to the dog crate, where the most important issues were the size of the crate and the sound level in the car when the police dogs bark. The main focus throughout the project has been to improve the dog crate regarding sound and size, even though other issues also have been investigated. Different concepts were made where most of them were evaluated end tested as prototypes in a V70 police car. The final result was a prototype for a new design of the dog crate including; the side panels, the front panel, the evacuation hatches, the partition wall and the ventilation for the dogs. It also resulted in a concept for securing the load in the back seat and a way to lock the boot in a half-open position. As for the regular police car it resulted in a concept for storage of the spike strip. The preliminary study also resulted in that from 2012-01-01 it is possible for the Swedish police to order the Volvo XC70 with a more powerful engine than ...